(untitled) (The Shivapuri Journal, 2026)
King Prithvi Narayan Shah of the Gorkha Kingdom pursued the unification of Nepal through a conscious integration of strategic vision, operational planning, and administrative foresight. He knew that success in warfare does not lie in mere numbers but in intelligence superiority, careful strategy, containment principles, tactical flexibility, and iron-fisted leadership. His campaigns epitomized the classical principles of Saam, Daam, Danda, and Bhed in a unified grand strategy that combines diplomacy, coercion, deception, and force. Notwithstanding Gorkha’s relative inferiority in resources as compared to the Baisi, Chaubisi, Sen, and Malla states, Shah turned it into the driving force of unification through systematic policies, detailed campaign planning, and strong administrative structures. Military operations were integrated with intelligence gathering, logistic preparation, psychological pressure, and preemptive maneuvering, which provided the basis for operational continuity with minimum resistance. No less important was Shah’s ability to generate loyalty and morale among soldiers and civilians in protracted campaigns. This paper examines the strategic, operational, and administrative dimensions of Shah’s conquest of the Kathmandu Valley, demonstrating how disciplined leadership, integrated planning, and coordinated use of multiple instruments of power enabled a small state to achieve decisive victories and lay the foundation for a unified Nepal. This paper is qualitative in nature and is based on descriptive and analytical methods of study, focusing mainly on secondary sources of data.